The university’s psychological services activities comparative analysis in Kazakhstan and China (Journal of Educational Sciences, 2023)
The article discusses the universities psychological services development history and foundations (psychological centers counseling) . The article purpose is in Kazakhstan and China the psychological services activities  comparative analysis of the identify similar features and specific features development of such services in these countries. In the article theoretical part, the services and centers in Kazakhstan and China formation features are considered, a in this area scientific research review is conducted. The universities psychological services development history analysis allows us to talk about the transition in the psychological services provision to students - from a medical paradigm to a sociocultural one. The Soviet and Chinese tradition of providing psychological services in universities originated in the twentieth century late 70s-early 80s. The historically established area of psychological support services activity for students is counseling, which is noted in both Western and Eastern traditions. Currently, the most popular activities of services and centers are education and counseling, although psychodiagnostic, preventive and psychocorrective activities are also declared. Kazakh and Chinese universities consider the psychological services/centers activities as a way to strengthen the students mental health and well-being. Modern psychological student support services have a separate office and conditionally work under the auspices of the Youth Social Affairs Departments. In the study practical part, the universities psychological services representatives survey was conducted.Key words: the university psychological service, the university consulting services center, students psychological counseling,  the services activities comparative analysis, counseling standards.